2000
DOI: 10.1063/1.480557
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations with constrained roto-translational motions: Theoretical basis and statistical mechanical consistency

Abstract: From a specific definition of the roto-translational ͑external͒ and intramolecular ͑internal͒ coordinates, a constrained dynamics algorithm is derived for removing the roto-translational motions during molecular dynamics simulations, within the leap-frog integration scheme. In the paper the theoretical basis of this new method and its statistical mechanical consistency are reported, together with two applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
122
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 11 publications
0
122
0
Order By: Relevance
“…The trajectories were then propagated for 20 ns in a NVT ensemble using an integration step of 2.0 fs with the rototranslational constrain (25) applied to the solute. It is worth noting that these simulations are, at least to our knowledge, the longest ever performed on such system.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The trajectories were then propagated for 20 ns in a NVT ensemble using an integration step of 2.0 fs with the rototranslational constrain (25) applied to the solute. It is worth noting that these simulations are, at least to our knowledge, the longest ever performed on such system.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Temperature has been controlled by the Berendsen's coupling algorithm with a time constant equal to the time step to approximate the Gaussian isokinetic thermostat. 41,42 Long-range electrostatic interactions have been calculated using the particle-mesh Ewald method and applying a cutoff of 0.9 nm to the short-range Lennard-Jones interactions. The SETTLE algorithm 43 is used to fix the water molecule geometry, and the SHAKE algorithm, 44 to constrain the O-H distance in the PVA hydroxylic groups.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Mathematical proof has been given that rotational degrees of freedom can be removed without affecting the statistical mechanical ensemble, 3 and it has been demonstrated that the use of an NDLP unit cell in conjunction with rotational constraints does not lead to detectable changes relative to simulations performed in a rhombic dodecahedron.…”
Section: ■ Introductionmentioning
confidence: 99%